COMPARATIVE ANALYSIS OF LEGISLATION ON CITIZEN PARTICIPATION IN PUBLIC ORDER PROTECTION AND PUBLIC SAFETY: THE EXPERIENCE OF KAZAKHSTAN, RUSSIA, BELARUS, AND TAJIKISTAN - Urazbaev Abatbay Askerbaevich (PEDAGOGS, 2025)
This study provides a comparative analysis of legislative frameworks governing citizen participation in public order protection and safety in Kazakhstan, Russia, Belarus, and Tajikistan. Rooted in the Soviet tradition of voluntary people’s patrols, or "druzhinas," these nations have adapted their systems to address modern challenges, balancing state coordination with civic initiative. By examining Kazakhstan’s Law No. 590 of 2004, Russia’s Federal Law No. 44-FZ of 2014, Belarus’s Law No. 214-Z of 2003, and Tajikistan’s Law No. 1969 of 2023, this paper explores the general principles guiding participation, the rights and duties of participants, the strengths and weaknesses of each system, and their legislative similarities and differences. Drawing on legal texts, official reports, and academic studies, the analysis highlights best practices – such as Russia’s regional adaptability, Kazakhstan’s focus on prevention, Belarus’s structured coordination, and Tajikistan’s culturally rooted councils – offering insights for mutual learning and enhanced collaboration within the Eurasian Economic Union (EAES) and Collective Security Treaty Organization (CSTO) frameworks.